Pengembangan Manajemen terhadap Kualitas Pelayanan UMKM Ayam Bakar di Cikarang Utara - Etty Zuliawati Zed; Muh Rofif Perdana; Firda Farida; Titin Oktaviana (Lembaga Pengembangan Kinerja Dosen, 2024)
This study aims to analyze the effect of management development on improving service quality in grilled chicken MSMEs. The research method used is a quantitative approach with survey techniques on a number of grilled chicken MSMEs. The results showed that management development, which includes aspects of resource management, operational system development, and customer satisfaction, has a significant effect on service quality. These findings are expected to be a reference for MSME players in increasing competitiveness through structured management improvements. The implication of this study is the importance of continuous management improvement in improving service quality.